Chitinase 3-Like Protein 1, Th 2 Cytokines (IL-4 and IL-13) in Incised and Lacerated Cutaneous Wounds: Experimental Study - Mohamed, Marwa; Hamed, Karima; Shalaby, Mohamed; Khalil, Wagdy; Ibrahim, Samah; Mahrous, Mai (International Journal of Medical Toxicology and Forensic Medicine, 2026)
Background: Wounds are associated with increased levels of inflammatory biomarkers. In forensic investigations, biomolecular analysis can help determine the age of a wound. This study aimed to estimate the levels of inflammatory biomarkers: chitinase 3-like 1 (CHI3L1), interleukin-4 (IL-4), and interleukin-13 (IL-13); and to correlate them with immunohistopathological effects. Methods: Cutaneous incisional (IW) and lacerated (LW) wounds were induced in thirty-six male rats, with eighteen rats allocated to each group. Tissue samples were collected at 4 and 8 days post-injury for histopathological, immunohistochemical, and biomolecular examinations. Results: IL-4, IL-13, and CHI3L1 demonstrated significant time-dependent upregulation, with expression levels rising four- to six-fold at days 4 and 8 post-injury (P<0.05). CHI3L1 showed a biphasic expression pattern, with peak expression on day 4. IW generally exhibited higher gene expression levels compared to LW. Conclusion: The biphasic time-dependent expression patterns of CHI3L1 in cutaneous injuries could be useful for wound age estimation, supporting their future application in medical and forensic contexts through further human clinical validation.